The Implementation of Role-Playing Method to Enhance Students’ Reading Interest in IPAS: A Qualitative Case Study in Elementary School - Tia Ihsantiani; Arnie Fajar; Eneng Martini (Educenter : Jurnal Ilmiah Pendidikan, 2026)
This study aims to examine the implementation of the role-playing method in enhancing reading interest among fifth-grade students in IPAS (Integrated Natural and Social Sciences) learning. This research employed a qualitative case study approach conducted in an elementary school in Indonesia, involving one teacher and 25 fifth-grade students as participants selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and document analysis, and analyzed using thematic analysis. The findings reveal that the role-playing method significantly enhances students’ reading interest by fostering active engagement, improving comprehension, and creating meaningful learning experiences. Students showed increased motivation to read as they were required to understand texts in order to perform assigned roles. In addition, role-playing promoted collaborative learning and strengthened students’ intrinsic motivation, particularly in terms of autonomy, competence, and relatedness. However, challenges were identified in classroom management and ensuring equal participation among students. This study contributes to the development of interactive pedagogical strategies in IPAS learning and highlights the potential of role-playing as an effective approach to promote reading interest in elementary education.